The Force of Absent Things: HIV/AIDS, PEPFAR Vietnam, and the Afterlife of Aid. Issue 4 (1st December 2018) - Montoya, Alfred
Abstract: This article examines emerging strategies employed by nongovernmental organizations working in HIV/AIDS prevention and control in Vietnam that have been put to work in the recent past in the context of precipitous declines in US funding for such work through the President's Emergency Plan for AIDS Relief (PEPFAR). These strategies foreground specific personalities in an instrumentalization of experience, expert knowledges, and identity in a delicate balance between projecting strength and indicating urgent need. These strategies are played out in the realm of social media, facilitated through information communications technologies (ICTs) that are quickly restructuring forms of sociality and the tradecraft of identity politics. These technologies and the strategies they enable turn on and modify a relatively new configuration of Homo sapiens that I have elsewhere termed the Human. This article explores its special usage in an Asian context in ICT-enabled networks, against the background of an epidemic and its looming projected increases in morbidity and mortality.